Tantalum carbide feed material, tantalum carbide product and preparation method thereof
By using a combination feed of tantalum carbide composite powder and wax-based binder, the problems of low solid phase content and poor storage stability of the tantalum carbide coating are solved, and a tantalum carbide coating with high density and excellent performance is achieved to meet the needs of the growth of high-purity semiconductor ceramic single crystals.
Patent Information
- Application Number
- CN202410980184.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-07-22
AI Technical Summary
In the existing methods for preparing tantalum carbide coatings, the mass fraction of tantalum carbide powder is difficult to be higher than 85 wt%, resulting in poor coating performance, and the raw materials are prone to phase separation during storage, which is difficult to meet the needs of long-term storage.
The combination of tantalum carbide composite powder and wax-based binder was fed. The mass fraction of tantalum carbide composite powder was 90 wt%~95 wt%, and the mass fraction of wax-based binder was 5 wt%~10 wt%. After intensive mixing, coating and sintering treatment was made to prepare a tantalum carbide coating with high density and excellent performance.
The high solid phase content and long-term storage stability of the tantalum carbide coating are achieved. The relative density of the coating can reach more than 98.5 wt%, and there are no defects such as cracks, meeting the needs of the growth of high-purity semiconductor ceramics.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of tantalum carbide materials, and in particular to a tantalum carbide feed material, a tantalum carbide product and a preparation method thereof. Background Art
[0002] Tantalum carbide (TaC) has excellent high-temperature mechanical stability, corrosion resistance, ablation resistance and other advantages. It can maintain structural and chemical stability even at high temperatures. It is an ideal substrate material for the growth of high-purity ceramic single crystals and can ensure the purity and quality of single crystal materials.
[0003] The preparation of high-performance tantalum carbide coatings often uses the method of sintering tantalum carbide coatings. At present, the raw materials used for sintering tantalum carbide coatings mainly use organic slurries with high solid content, that is, tantalum carbide powder particles and a small amount of sintering aids are dispersed in an organic solvent. This method mainly has the following two problems: (1) The organic solvent needs to maintain a certain fluidity, which will make it difficult for the mass fraction of tantalum carbide powder to be higher than 85wt%. The tantalum carbide solid content of the obtained tantalum carbide coating is low, and the performance of the coating is poor; (2) The density of tantalum carbide is as high as 14.3g / cm3, and phase separation is prone to occur during the storage process, resulting in the performance of the raw organic slurry being reduced or even unusable, and cannot meet the needs of long-term storage. Summary of the invention
[0004] Based on this, it is necessary to provide a tantalum carbide feed and a preparation method thereof that can increase the solid content of the tantalum carbide coating and can be stored for a long time, as well as to provide a tantalum carbide product and a preparation method thereof that has a simple preparation process and excellent performance.
[0005] In a first aspect of the present application, a tantalum carbide feed is provided:
[0006] The invention comprises 90% to 95% by mass of tantalum carbide composite powder and 5% to 10% by mass of a wax-based binder, wherein the tantalum carbide composite powder comprises tantalum carbide powder and a sintering aid.
[0007] In some embodiments, the mass ratio of the sintering aid to the tantalum carbide powder is 1:99 to 5:95.
[0008] In some embodiments, the particle size of the tantalum carbide powder is 0.2 μm to 3.0 μm.
[0009] In some embodiments, the sintering aid satisfies one or more of the following conditions:
[0010] (1) The sintering aid includes at least one of tantalum disilicide, molybdenum disilicide, pyrolytic carbon black, aluminum oxide and yttrium oxide;
[0011] (2) The particle size of the sintering aid is 0.5 μm to 5.0 μm.
[0012] In some embodiments, the wax-based binder includes, by weight, 70 to 90 parts of filler, 5 to 25 parts of backbone binder, and 2 to 6 parts of dispersant.
[0013] In some embodiments, the filler comprises at least one of carnauba wax, microcrystalline wax, paraffin wax and polyethylene wax; and / or,
[0014] The backbone binder comprises at least one of high-density polyethylene, polypropylene and ethylene-vinyl acetate copolymer; and / or,
[0015] The dispersing agent includes stearic acid.
[0016] In a second aspect of the present application, a method for preparing the above-mentioned tantalum carbide feed is provided, comprising the following steps:
[0017] Mixing the tantalum carbide powder with the sintering aid to obtain the tantalum carbide composite powder;
[0018] The tantalum carbide composite powder and the wax-based binder are kneaded.
[0019] In a third aspect of the present application, a method for preparing a tantalum carbide product is provided, comprising the following steps:
[0020] The tantalum carbide feed material is melted and coated on the surface of the substrate to obtain a preform, wherein the preform includes the substrate and a coating layer located on the surface of the substrate,
[0021] The preform is subjected to degreasing and sintering treatment to obtain a tantalum carbide product, wherein the tantalum carbide product comprises the substrate and a tantalum carbide coating, wherein the tantalum carbide coating is bonded to at least a portion of the surface of the substrate.
[0022] In some embodiments, one or more of the following conditions are met:
[0023] (1) The substrate includes a graphite crucible and a graphite sintered boat;
[0024] (2) The thickness of the coating layer is 50 μm to 120 μm;
[0025] (3) The thickness of the coating layer after the sintering process is 30 μm to 100 μm.
[0026] In some embodiments, one or more of the following conditions are met:
[0027] (1) The degreasing comprises: placing the preform in a n-heptane or n-hexane solvent and soaking it at 20°C to 50°C for 15 min to 30 min; or, in a protective gas atmosphere, heating the preform to 400°C to 500°C at a heating rate of 2°C / min to 5°C / min and keeping the temperature for 30 min to 60 min;
[0028] (2) The sintering treatment includes: in a protective gas atmosphere, heating the degreased preform to 2000°C~2200°C at a heating rate of 2°C / min~5°C / min, and keeping the temperature for 0.8h~1.2h.
[0029] In a fourth aspect of the present application, there is provided a tantalum carbide product, comprising a tantalum carbide product prepared by the above-mentioned method for preparing the tantalum carbide product, wherein the tantalum carbide product comprises the substrate and the tantalum carbide coating, and the tantalum carbide coating is bonded to at least a portion of the surface of the substrate.
[0030] In some embodiments, the thickness of the tantalum carbide coating is 30 μm to 100 μm.
[0031] This application has the following beneficial effects:
[0032] The tantalum carbide feed material of the present application uses a wax-based binder with good surface affinity to tantalum carbide to replace the organic solvent, and the mass fraction of the tantalum carbide composite powder is as high as 90wt%~95wt%. The tantalum carbide feed material can be used to prepare a tantalum carbide coating with high density. The tantalum carbide feed material of the present application does not contain an organic solvent, which avoids the internal stress caused by solvent volatilization during the preparation of large-sized tantalum carbide coatings, and can obtain a tantalum carbide coating with fewer cracks. The tantalum carbide feed material of the present application can maintain the form of solid particles during the storage process, and can still be used to prepare tantalum carbide coatings with good uniformity after long-term storage.
[0033] The relative density of the tantalum carbide coating of the tantalum carbide product of the present application can reach more than 98.5wt%, and there are no defects such as cracks, high reliability, and can fully meet the needs of high-purity semiconductor ceramic single crystal growth. In addition, the preparation process of the tantalum carbide product is simple, efficient, and conducive to industrial mass production. It is the preferred preparation method for preparing sintered tantalum carbide coatings and products thereof. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0035] In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In this application, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0037] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0038] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0039] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.
[0040] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0041] The melting point of tantalum carbide is as high as 3880℃. It has chemical stability and corrosion resistance far higher than SiC and BN in high temperature environment. It can withstand the erosion of almost all acids, alkalis and salt substances in a reducing atmosphere. Tantalum carbide has good chemical and mechanical compatibility with carbon materials and can effectively protect carbon materials. It is an ideal substrate material for the growth of high-purity ceramic single crystals.
[0042] At present, the methods commonly used to prepare high-performance tantalum carbide coatings are mainly sintered tantalum carbide coatings and chemical vapor deposition. The tantalum carbide coating prepared by chemical vapor deposition has the advantages of uniform thickness, controllable grain structure, and high purity, but the equipment required for this method is expensive and the operating cost is high. The prepared coating is also prone to cracks and pores, resulting in low reliability of the tantalum carbide coating. Sintered tantalum carbide coating has the advantages of simple operation, low cost, and mass production, and has become the preferred method for preparing high-performance tantalum carbide coatings.
[0043] At present, sintered tantalum carbide coatings mainly use organic slurries with high solid content, that is, tantalum carbide powder particles and a small amount of sintering aids are dispersed in an organic solvent; then the organic slurry is sprayed or brushed on the surface of a graphite crucible, and the tantalum carbide coating can be obtained after high-temperature sintering. However, the organic slurry needs to maintain a certain fluidity, and the mass fraction of tantalum carbide powder is difficult to be higher than 85wt%, otherwise it will cause the resulting coating to crack. In addition, tantalum carbide organic slurry is prone to sedimentation of ceramic powder particles during storage. Although adding ceramic dispersants or using modified tantalum carbide ceramic powders can improve the stability of organic slurries, the sedimentation of tantalum carbide is still inevitable during long-term storage, resulting in poor use of the slurry.
[0044] In a first aspect of the present application, a tantalum carbide feed is provided, whose components include tantalum carbide composite powder and a wax-based binder, the mass fraction of the tantalum carbide composite powder is 90wt%~95wt%, the mass fraction of the wax-based binder is 5wt%~10wt%, and the tantalum carbide composite powder includes tantalum carbide powder and a sintering aid.
[0045] Optionally, the mass fraction of the tantalum carbide composite powder is 90wt%~95wt%, including but not limited to: 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%.
[0046] Optionally, the mass fraction of the wax-based binder is 5wt%~10wt%, including but not limited to: 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%.
[0047] In some embodiments, the mass ratio of the sintering aid to the tantalum carbide powder is 1:99 to 5:95, including but not limited to 1:99, 3:99, 5:99, 5:97, and 5:95.
[0048] It is understandable that adding a small amount of sintering aid to the tantalum carbide feed can help improve the density of the coating after sintering, but if too much is added, it may affect the compatibility of the tantalum carbide feed and cause microcracks in the obtained coating. In addition, it is necessary to select the appropriate type of sintering aid according to the specific application scenario.
[0049] In some embodiments, the purity of the tantalum carbide powder is higher than 99.99%, and the particle size is 0.2 μm to 3.0 μm, including but not limited to: 0.2 μm, 0.8 μm, 1.4 μm, 2 μm, 2.5 μm, and 3 μm.
[0050] It is understandable that the particle size of tantalum carbide powder has an important influence on the performance of tantalum carbide feed. When the particle size of tantalum carbide powder is too large, it will be difficult for tantalum carbide feed to fill the fine pores in the coating, and the density of the resulting coating is low. When the particle size of tantalum carbide powder is too small, the tantalum carbide powder in the tantalum carbide feed is prone to agglomeration, thereby reducing the performance of the coating. Under the composition of the tantalum carbide feed of the present application, selecting the tantalum carbide powder particle size within the above range helps to obtain a tantalum carbide coating with higher density later.
[0051] In some embodiments, the sintering aid includes at least one of tantalum disilicide, molybdenum disilicide, pyrolytic carbon black, aluminum oxide, and yttrium oxide.
[0052] In some embodiments, the particle size of the sintering aid powder is 0.5 μm to 5.0 μm.
[0053] Optionally, the purity of the sintering aid powder is higher than 99.99%, and the particle size is 0.5 μm to 5.0 μm, including but not limited to: 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm.
[0054] In some embodiments, the wax-based binder comprises, by weight, 70 to 90 parts of filler, 5 to 25 parts of backbone binder, and 2 to 6 parts of dispersant.
[0055] Optionally, the filler includes at least one of carnauba wax, microcrystalline wax, sliced paraffin wax, and polyethylene wax, including 70 parts to 90 parts, including but not limited to 70 parts, 75 parts, 80 parts, 85 parts, and 90 parts.
[0056] Optionally, the backbone binder includes at least one of high-density polyethylene, polypropylene and ethylene-vinyl acetate copolymer, and the backbone binder includes 5 parts to 25 parts, including but not limited to: 5 parts, 10 parts, 15 parts, 20 parts, and 25 parts.
[0057] Optionally, the dispersant includes stearic acid, and the stearic acid includes 2 parts to 6 parts, including but not limited to: 2 parts, 3 parts, 4 parts, 5 parts, and 6 parts.
[0058] It can be understood that the wax-based binder has good surface affinity with the tantalum carbide powder, so that when the tantalum carbide powder content is high, the tantalum carbide powder can still be evenly dispersed in the feed and is not easy to agglomerate. The dispersant is used to further improve the compatibility of tantalum carbide and the wax-based binder. The backbone binder is used to improve the forming strength of the tantalum carbide feed. The amount of the backbone binder added should not be too much, otherwise it may affect the subsequent degreasing process of the tantalum carbide coating preform.
[0059] In a second aspect of the present application, a method for preparing the above-mentioned tantalum carbide feed is provided, comprising the following preparation steps:
[0060] mixing tantalum carbide powder with a sintering aid to obtain tantalum carbide composite powder;
[0061] Tantalum carbide composite powder and wax-based binder are mixed together.
[0062] Optionally, tantalum carbide powder and sintering aid are placed in a ceramic ball mill, zirconium oxide balls are added, the ball milling medium includes anhydrous ethanol, the ball-to-material ratio is 1:1~10:1, the ball milling time is 8h~24h, and the ball milling speed is 50r / min~200r / min; after ball milling, the mixed slurry is vacuum dried and sieved, and then sealed.
[0063] Optionally, the ball-to-material ratio is 1:1~10:1, including but not limited to: 1:1, 1:3, 1:5, 1:8, 1:10.
[0064] Optionally, the ball milling time is 8 h to 24 h, including but not limited to: 8 h, 12 h, 16 h, 20 h, 24 h.
[0065] Optionally, the ball mill rotation speed is 50 r / min~200 r / min, including but not limited to: 50 r / min, 100 r / min, 150 r / min, 200 r / min.
[0066] Optionally, the vacuum drying temperature is 60°C to 80°C, including but not limited to: 60°C, 65°C, 70°C, 75°C, 80°C.
[0067] Optionally, the insulation time is 6 to 24 hours, including but not limited to: 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours.
[0068] Optionally, the mesh size of the sieving is 200-400 mesh, including but not limited to 200 mesh, 250 mesh, 300 mesh, 350 mesh, and 400 mesh.
[0069] Optionally, the tantalum carbide composite powder and the wax-based binder are mixed by banburying at a temperature of 120°C to 160°C, including but not limited to 120°C, 130°C, 140°C, 150°C, and 160°C; the banburying time is 30min to 90min, including but not limited to 30min, 40min, 50min, 60min, 70min, 80min, and 90min.
[0070] In some embodiments, after kneading the tantalum carbide composite powder and the wax-based binder, the process further includes granulating or crushing the tantalum carbide feed.
[0071] Optionally, the granulation temperature is 80°C~120°C, including but not limited to 80°C, 90°C, 100°C, 110°C, 120°C; the particle diameter is 2mm~5mm, including but not limited to: 2mm, 3mm, 4mm, 5mm; the particle length is 2~5mm, including but not limited to: 2mm, 3mm, 4mm, 5mm.
[0072] Optionally, the crushed particles need to be sieved with a mesh size of 20 to 40, including but not limited to: 20 mesh, 25 mesh, 30 mesh, 35 mesh, and 40 mesh.
[0073] In a third aspect of the present application, a method for preparing a tantalum carbide product is provided, comprising the following steps:
[0074] The molten tantalum carbide feed material is coated on the surface of the substrate to obtain a preform, which includes a substrate and a coating layer on the surface of the substrate.
[0075] The preform is degreased and sintered to obtain a tantalum carbide product, which includes a substrate and a tantalum carbide coating, wherein the tantalum carbide coating is bonded to at least a portion of the surface of the substrate.
[0076] In some embodiments, the tantalum carbide feed is heated to 120°C~150°C, including but not limited to: 120°C, 130°C, 140°C, 150°C; the substrate is heated to 80~120°C, including but not limited to: 80°C, 90°C, 100°C, 110°C, 120°C; the molten tantalum carbide feed is coated on the surface of the substrate, and the coating thickness is controlled to be 50μm~100μm, including but not limited to: 50μm, 60μm, 70μm, 80μm, 90μm, 100μm.
[0077] In some embodiments, the substrate includes a graphite crucible and a graphite boat.
[0078] In some embodiments, degreasing includes: placing the preform in a n-heptane or n-hexane solvent, soaking it at 20°C to 50°C for 15min to 30min, including but not limited to: 15min, 20min, 25min, 30min; or, in a protective gas atmosphere, heating the preform to 400°C to 500°C at a heating rate of 2°C / min to 5°C / min, and keeping it warm for 30min to 60min, including but not limited to: 30min, 40min, 50min, 60min;
[0079] It is understandable that the preform needs to be degreased before sintering. If the degreasing is not complete, the surface of the resulting coating may have many cracks. Most of the wax in the coating can be removed by degreasing in a solvent, and the remaining binder components in the coating can be removed by heating degreasing. The use of solvent degreasing combined with heating degreasing can significantly shorten the degreasing process time and make the coating after sintering have fewer cracks.
[0080] In some embodiments, the sintering process includes: heating to 2000-2200° C. at a heating rate of 2-5° C. / min under an inert gas atmosphere, and keeping the temperature for 0.8 h-1.2 h.
[0081] Optionally, the heating rate of the sintering treatment is 2℃ / min~5℃ / min, including but not limited to: 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min; the holding temperature is 2000℃~2200℃, including but not limited to: 2000℃, 2100℃, 2200℃; the holding time is 0.8h~1.2h, including but not limited to: 0.8h, 0.9h, 1h, 1.1h, 1.2h.
[0082] In some embodiments, the coating layer has a thickness of 50 μm to 120 μm; the coating layer after sintering has a thickness of 30 μm to 100 μm, including but not limited to: 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm. The coating layer will become denser during the sintering process, and the thickness of the coating layer will decrease compared to before sintering.
[0083] In a fourth aspect of the present application, a tantalum carbide product is provided, which is prepared by the above-mentioned method for preparing tantalum carbide products. The tantalum carbide product includes a substrate and a tantalum carbide coating, and the tantalum carbide coating is bonded to at least a portion of the surface of the substrate.
[0084] In some embodiments, the thickness of the tantalum carbide coating is between 30 μm and 100 μm.
[0085] The present application is further described in detail below in conjunction with specific embodiments.
[0086] In the following specific embodiments and comparative examples, the raw materials used, unless otherwise specified, are all commercially available products; the instruments used, unless otherwise specified, are all commercially available products; and the processes used, unless otherwise specified, are all routinely selected by those skilled in the art.
[0087] Among them, commercial high-purity tantalum carbide powder is selected with a purity of 99.99%, commercial sintering aid powders such as tantalum disilicide, molybdenum disilicide, pyrolytic carbon black, and alumina are selected with a purity of 99.99%, and commercial paraffin, carnauba wax, high-density polyethylene, polypropylene, ethylene-vinyl acetate copolymer and stearic acid are selected.
[0088] The relative density is tested by the following method: the density of the tantalum carbide coating is tested by the ceramic coating density test method of GB / T 39688-2020, and the relative value of the tantalum carbide coating density relative to the theoretical pure tantalum carbide coating density is calculated.
[0089] The coating quality is tested by the following method: the tantalum carbide coating sample is subjected to industrial CT scanning, and the distribution at the scanning interface is observed. If there are no surface defects (pores or cracks) larger than 2μm, the coating quality is judged to be intact.
[0090] Example 1
[0091] (1) The preparation of tantalum carbide feed includes the following steps:
[0092] Tantalum carbide powder and molybdenum disilicide powder were placed in a ceramic ball mill, zirconium oxide balls were added, the ball-to-material ratio was 8:1, the ball milling time was 12 hours, and the ball milling speed was 80r / min; after ball milling, the mixed slurry was vacuum dried and sieved. Among them, the particle size of tantalum carbide powder was 0.5μm, the particle size of molybdenum disilicide powder was 1.0μm, and the mass ratio of tantalum carbide powder to molybdenum disilicide powder was 99:1; the vacuum drying temperature was 60℃, the heat preservation time was 6 hours; the mesh size of the sieve was 200 meshes.
[0093] Tantalum carbide composite powder and wax-based binder are mixed by banburying. The mass fraction of tantalum carbide composite powder is 91wt%, and the mass fraction of wax-based binder is 9wt%. The mass fraction composition of wax-based binder is as follows: filler is 75wt% carnauba wax; backbone binder is 20wt% high-density polyethylene, and dispersant is 5wt% stearic acid; banburying temperature is 150℃, and banburying time is 30min.
[0094] After being mixed uniformly by internal kneading, granulation is performed to obtain tantalum carbide feed material, wherein the granulation temperature is 100° C., the particle diameter is 3 mm, and the particle length is 5 mm.
[0095] (2) The preparation of tantalum carbide products includes the following steps:
[0096] The graphite crucible is heated to 120°C, the tantalum carbide feed is heated to 150°C until it melts, and the molten tantalum carbide feed is coated on the surface of the graphite crucible, and the coating thickness is controlled to be 80μm. The preform is placed in a n-heptane solvent at a temperature of 30°C for 20 minutes; the temperature is raised to 450°C under a protective atmosphere for 30 minutes; the temperature is raised to 2150°C and sintered for 1 hour to obtain a graphite crucible with a highly dense tantalum carbide coating. The atmosphere of the degreasing process is argon, and the heating rate is 2°C / min; the atmosphere of the sintering process is argon, and the heating rate is 3°C / min.
[0097] The relative density of the tantalum carbide coating prepared in this embodiment reaches 98.9%, the thickness of the tantalum carbide coating is 68 μm, and there are no defects such as cracks on the coating surface.
[0098] Example 2
[0099] The preparation of tantalum carbide feedstock includes the following steps:
[0100] Tantalum carbide powder and molybdenum disilicide powder were placed in a ceramic ball mill, zirconium oxide balls were added, the ball-to-material ratio was 5:1, the ball milling time was 16 hours, and the ball milling speed was 100r / min; after ball milling, the mixed slurry was vacuum dried and sieved. Among them, the particle size of tantalum carbide powder was 2.5μm, the particle size of molybdenum disilicide powder was 3.0μm, and the mass ratio of tantalum carbide powder to molybdenum disilicide powder was 98:1; the vacuum drying temperature was 60℃, the heat preservation time was 6 hours; the mesh size of the sieve was 200 meshes.
[0101] Tantalum carbide composite powder and wax-based binder are mixed by banburying. The mass fraction of tantalum carbide composite powder is 92wt%, and the mass fraction of wax-based binder is 8wt%; the mass fraction composition of wax-based binder is as follows: filler is 85wt% carnauba wax; backbone binder is 5wt% high-density polyethylene, 5wt% ethylene-vinyl acetate copolymer, and dispersant is 5wt% stearic acid; banburying temperature is 130℃, and banburying time is 40min.
[0102] After being mixed uniformly by internal kneading, the mixture is crushed and passed through a 20-mesh filter to obtain tantalum carbide feed.
[0103] (2) The preparation of tantalum carbide products includes the following steps:
[0104] The graphite crucible is heated to 110°C, the tantalum carbide feed is heated to 140°C until it melts, and the molten tantalum carbide feed is coated on the surface of the graphite crucible, and the coating thickness is controlled to be 80μm. The preform is placed in a n-heptane solvent at a temperature of 40°C for 15 minutes; the temperature is raised to 420°C under a protective atmosphere for 30 minutes; the temperature is raised to 2100°C and sintered for 1 hour to obtain a graphite crucible with a highly dense tantalum carbide coating. The atmosphere of the degreasing process is argon, and the heating rate is 2°C / min; the atmosphere of the sintering process is argon, and the heating rate is 3°C / min.
[0105] The relative density of the tantalum carbide coating prepared in this embodiment is 98.8%, the thickness of the tantalum carbide coating is 70 μm, and there are no defects such as cracks on the coating surface.
[0106] Example 3
[0107] The preparation of tantalum carbide feedstock includes the following steps:
[0108] Tantalum carbide powder and molybdenum disilicide powder were placed in a ceramic ball mill, zirconium oxide balls were added, the ball-to-material ratio was 3:1, the ball milling time was 16 hours, and the ball milling speed was 80r / min; after ball milling, the mixed slurry was vacuum dried and sieved. Among them, the particle size of tantalum carbide powder was 0.5μm, the particle size of molybdenum disilicide powder was 2.0μm, and the mass ratio of tantalum carbide powder to molybdenum disilicide powder was 99:1; the vacuum drying temperature was 60℃, the heat preservation time was 6 hours; the mesh size of the sieve was 200 meshes.
[0109] Tantalum carbide composite powder and wax-based binder are mixed by banburying. The mass fraction of tantalum carbide composite powder is 91wt%, and the mass fraction of wax-based binder is 9wt%. The mass fraction composition of wax-based binder is as follows: filler is 75wt% carnauba wax; backbone binder is 20wt% high-density polyethylene, and dispersant is 5wt% stearic acid; banburying temperature is 120℃, and banburying time is 30min.
[0110] After being mixed uniformly by internal kneading, granulation is performed to obtain tantalum carbide feed material, wherein the granulation temperature is 100° C., the particle diameter is 3 mm, and the particle length is 5 mm.
[0111] (2) The preparation of tantalum carbide products includes the following steps:
[0112] The graphite crucible is heated to 120°C, the tantalum carbide feed is heated to 150°C until it melts, and the molten tantalum carbide feed is coated on the surface of the graphite crucible, and the coating thickness is controlled to be 80μm. The preform is placed in a n-heptane solvent at a temperature of 30°C for 20 minutes; the temperature is raised to 450°C under a protective atmosphere for 30 minutes; the temperature is raised to 2150°C and sintered for 1 hour to obtain a graphite crucible with a highly dense tantalum carbide coating. The atmosphere of the degreasing process is argon, and the heating rate is 2°C / min; the atmosphere of the sintering process is argon, and the heating rate is 3°C / min.
[0113] The relative density of the tantalum carbide coating prepared by this technical method reaches 99.0%, the thickness of the tantalum carbide coating is 67 μm, and there are no defects such as cracks on the coating surface.
[0114] Example 4
[0115] The preparation of tantalum carbide feedstock includes the following steps:
[0116] Tantalum carbide powder and molybdenum disilicide powder were placed in a ceramic ball mill, zirconium oxide balls were added, the ball-to-material ratio was 3:1, the ball milling time was 16 hours, and the ball milling speed was 80r / min; after ball milling, the mixed slurry was vacuum dried and sieved. Among them, the particle size of tantalum carbide powder was 0.5μm, the particle size of molybdenum disilicide powder was 1.0μm, and the mass ratio of tantalum carbide powder to molybdenum disilicide powder was 99:1; the vacuum drying temperature was 60℃, the heat preservation time was 6 hours; the mesh size of the sieve was 200 meshes.
[0117] Tantalum carbide composite powder and wax-based binder are mixed by internal kneading. The mass fraction of tantalum carbide composite powder is 93wt%, and the mass fraction of wax-based binder is 7wt%; the mass fraction composition of wax-based binder is as follows: filler is 90wt% carnauba wax; backbone binder is 8wt% polypropylene, and dispersant is 2wt% stearic acid; internal kneading temperature is 120℃, and internal kneading time is 40min.
[0118] After being mixed uniformly by internal kneading, granulation is performed to obtain tantalum carbide feed material, wherein the granulation temperature is 80° C., the particle diameter is 3 mm, and the particle length is 5 mm.
[0119] (2) The preparation of tantalum carbide products includes the following steps:
[0120] The graphite crucible is heated to 130°C, the tantalum carbide feed is heated to 130°C until it melts, and the molten tantalum carbide feed is coated on the surface of the graphite crucible, and the coating thickness is controlled to be 70μm. The preform is placed in a n-heptane solvent at a temperature of 30°C for 20 minutes; the temperature is raised to 450°C under a protective atmosphere for 30 minutes; the temperature is raised to 2150°C and sintered for 1 hour to obtain a graphite crucible with a highly dense tantalum carbide coating. The atmosphere of the degreasing process is argon, and the heating rate is 2°C / min; the atmosphere of the sintering process is argon, and the heating rate is 3°C / min.
[0121] The relative density of the tantalum carbide coating prepared in this embodiment is 99.2%, the thickness of the tantalum carbide coating is 62 μm, and there are no defects such as cracks on the coating surface.
[0122] Example 5
[0123] The preparation methods of this example are basically the same as those of Example 1, except that the particle size of tantalum carbide selected in this comparative example is 4 μm.
[0124] The relative density of the tantalum carbide coating prepared in this embodiment is 98.5%, the thickness of the tantalum carbide coating is 68 μm, and there are a small amount of pores on the surface of the coating.
[0125] Comparative Example 1
[0126] The preparation method of this comparative example is basically the same as that of Example 1, except that no sintering aid is added to the tantalum carbide powder.
[0127] The relative density of the tantalum carbide coating prepared in this comparative example is 95.6%, the thickness of the tantalum carbide coating is 65 μm, and there are many pores on the surface of the coating.
[0128] Comparative Example 2
[0129] The preparation method of this comparative example is basically the same as that of Example 2, except that the filler in the wax-based binder is 55 wt % carnauba wax, and the backbone binder is 35 wt % high-density polyethylene.
[0130] The relative density of the tantalum carbide coating prepared in this comparative example is 96.8%, the thickness of the tantalum carbide coating is 65 μm, and cracks exist on the surface of the coating.
[0131] The performance test data of each embodiment and comparative example are shown in Table 1:
[0132] Table 1
[0133]
[0134] It can be seen from Table 1 that the tantalum carbide coatings prepared in Examples 1-5 have a higher relative density, indicating that the coatings have a higher density, and the obtained coatings have fewer pores and excellent coating quality. The obtained coatings can meet the needs of high-purity semiconductor ceramic single crystal growth. Compared with Example 1, since no sintering aid is added, the relative density of the obtained tantalum carbide coating is significantly reduced, and more pores appear on the surface of the coating, which is difficult to meet the needs of high-purity semiconductor ceramic single crystal growth. Compared with Example 2, Comparative Example 2 changes the mass ratio of each component of the wax-based binder. Due to the low filler content, it is not conducive to the formation of uniformly dispersed tantalum carbide feed; due to the high content of the backbone binder, the preform is incompletely degreased. The tantalum carbide coating obtained in Comparative Example 2 has a lower relative density, and cracks appear on the surface, which can no longer meet the needs of high-purity semiconductor ceramic single crystal growth.
[0135] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0136] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.
Claims
1. A tantalum carbide feed material, characterized in that: The invention is composed of 90% to 95% by mass of a tantalum carbide composite powder and 5% to 10% by mass of a wax-based binder, wherein the tantalum carbide composite powder includes tantalum carbide powder and a sintering aid; the particle size of the tantalum carbide powder is 0.2 μm to 3.0 μm; and the mass ratio of the sintering aid to the tantalum carbide powder is 1:99 to 5:95; The wax-based binder includes 70 to 90 parts of filler, 5 to 25 parts of backbone binder and 2 to 6 parts of dispersant by weight; The filler comprises at least one of carnauba wax, microcrystalline wax, paraffin wax and polyethylene wax; The backbone binder includes at least one of high-density polyethylene, polypropylene and ethylene-vinyl acetate copolymer.
2. Tantalum carbide feed material according to claim 1, characterized in that The sintering aid includes at least one of tantalum disilicide, molybdenum disilicide, pyrolytic carbon black, aluminum oxide and yttrium oxide.
3. Tantalum carbide feed material according to claim 1 or 2, characterized in that The particle size of the sintering aid is 0.5 μm to 5.0 μm.
4. Tantalum carbide feed material according to claim 1 or 2, characterized in that The dispersing agent includes stearic acid.
5. A method for preparing a tantalum carbide feed material according to any one of claims 1 to 4, characterized in that: The steps include: Mixing the tantalum carbide powder with the sintering aid to obtain the tantalum carbide composite powder; The tantalum carbide composite powder and the wax-based binder are kneaded.
6. A method for preparing a tantalum carbide product, characterized in that: The steps include: The tantalum carbide feed material according to any one of claims 1 to 4 is melted and coated on the surface of a substrate to obtain a preform, wherein the preform comprises the substrate and a coating layer located on the surface of the substrate, The preform is subjected to degreasing and sintering treatments to obtain a tantalum carbide product, wherein the tantalum carbide product comprises the substrate and a tantalum carbide coating, wherein the tantalum carbide coating is bonded to at least a portion of the surface of the substrate.
7. The method for preparing a tantalum carbide product according to claim 6, characterized in that: The substrate includes a graphite crucible and a graphite boat.
8. The method for preparing a tantalum carbide product according to claim 6, characterized in that: The coating layer has a thickness of 50 μm to 120 μm.
9. The method for preparing a tantalum carbide product according to claim 6, characterized in that: The thickness of the coating layer after the sintering process is 30 μm to 100 μm.
10. The method for preparing a tantalum carbide product according to any one of claims 6 to 9, characterized in that: One or more of the following conditions are met: (1) The degreasing comprises: placing the preform in a n-heptane or n-hexane solvent and soaking it at 20°C to 50°C for 15 min to 30 min; or, in a protective gas atmosphere, heating the preform to 400°C to 500°C at a heating rate of 2°C / min to 5°C / min and keeping the temperature for 30 min to 60 min; (2) The sintering treatment includes: in a protective gas atmosphere, heating the degreased preform to 2000°C~2200°C at a heating rate of 2°C / min~5°C / min, and keeping the temperature for 0.8h~1.2h.
11. A tantalum carbide product, characterized in that: The tantalum carbide product is prepared by the preparation method described in any one of claims 6 to 10, comprising the substrate and the tantalum carbide coating, wherein the tantalum carbide coating is bonded to at least a portion of the surface of the substrate.
12. The tantalum carbide product according to claim 11, characterized in that The thickness of the tantalum carbide coating is 30 μm to 100 μm.
Citation Information
Patent Citations
Low-cost tantalum carbide coating preparation method
CN106699228A
Tantalum carbide slurry, tantalum carbide coating, preparation method of tantalum carbide coating and crucible
CN118063214A
Method of injection for the thin and parts
KR1020040092895A